Skin Byproducts of Reinhardtius hippoglossoides (Greenland Halibut) as Ecosustainable Source of Marine Collagen - Eva Martins; Rita Fernandes; Ana L. Alves; Rita O. Sousa; Rui L. Reis; Tiago H. Silva (Applied Sciences, 2022)
Collagen is a ubiquitous protein present in the extracellular matrix of all major metazoan animals, with approximately 28 different human collagen types described in the literature, each with unique physicochemical properties. Collagens found broad application in the cosmeceutical, pharmaceutical, and biomedical fields and can be isolated from environmentally sustainable sources such as marine byproducts, which are abundant in the fish processing industry and are highly appealing low-cost sources. In this study, marine collagen was isolated from the skins of Greenland halibut (Reinhardtius hippoglossoides), an unexplored byproduct from fish processing plants, using three different collagen extraction methods, due to the use of distinct salting-out methods using a solution of 2.6 M NaCl + 0.05 M Tris-HCl pH = 7.5, (method I); a combination of 0.7 M NaCl followed by a solution of 2.3 M NaCl + 0.05 M Tris-HCl pH = 7.5 (method II); and one method using only 0.9 M NaCl (method III), yielding COLRp_I, COLRp_II, and COLRp_III collagens. These extracted type I collagens were produced with a yield of around 2 and 4% and characterized regarding the physicochemical properties, considering possible biotechnological applications. This work evidenced that the typical triple helix structure conformation was preserved in all extraction methods, but influenced the thermal behavior, intrinsic morphology, and moisture capacity of the collagens, with interest for biotechnological application, as the incorporation as an ingredient in cosmetic formulation. Furthermore, the use of collagen isolated from skin byproducts represents a high economic value with decreasing collagen cost for industrial purposes and is also an environmentally sustainable source for industrial uses.